Hybridní revaskularizace myokardu - pohled kardiologa - Horák, Jan; Šimek, Stanislav; Kovárník, Tomáš; Semrád, Michal; Lindner, Jaroslav; Linhart, Aleš (Cor et Vasa (Brno), 2012)
This article summarizes current knowledge on the mutual position of surgical and interventional treatment of patients with multivessel coronary artery disease. It focuses on the possibilities of their combined use – so called hybrid myocardial revascularization. The use of minimally invasive surgery combined with current technologies of coronary interventions offers new opportunities, taking advantages of both procedures and eliminating some of their disadvantages. This previously rarely used technique could improve the clinical outcomes and treatment comfort in selected groups of patients.
Keywords: metaanalýza jako téma; Myocardial Revascularization; Humans; arteria mammaria; perkutánní koronární intervence; Combined Modality Therapy; Drug-Eluting Stents; koronární cévy; Meta-Analysis as Topic; diabetes mellitus; stenty uvolňující léky; aortokoronární bypass; miniinvazivní chirurgické výkony; koronární bypass; kombinovaná terapie; Minimally Invasive Surgical Procedures; Coronary Artery Bypass; minimálně invazivní chirurgie; Diabetes Mellitus; lidé; Coronary Vessels; revaskularizace myokardu